2020
DOI: 10.3389/fmicb.2020.01068
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Interactive Compounds From Pistacia lentiscus L. Thwart Pseudomonas aeruginosa Virulence

Abstract: Pseudomonas aeruginosa is capable to deploy a collection of virulence factors that are not only essential for host infection and persistence, but also to escape from the host immune system and to become more resistant to drug therapies. Thus, developing anti-virulence agents that may directly counteract with specific virulence factors or disturb higher regulatory pathways controlling the production of virulence armories are urgently needed. In this regard, this study reports that Pistacia lentiscus L. fruit cy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…The reduced pqsE gene expression would therefore disrupt the RhlR-mediated virulence gene expression. Additionally, the down-regulation of pqsBCDE will lead to quenching of the pqs system in P. aeruginosa and further contribute to reduced virulence (Deziel et al, 2005;Tahrioui et al, 2020). Collectively, all these evidences indicated that TRQ treatment could effectively target the pqs system and subsequently contribute to the inhibition of QS systems in P. aeruginosa.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The reduced pqsE gene expression would therefore disrupt the RhlR-mediated virulence gene expression. Additionally, the down-regulation of pqsBCDE will lead to quenching of the pqs system in P. aeruginosa and further contribute to reduced virulence (Deziel et al, 2005;Tahrioui et al, 2020). Collectively, all these evidences indicated that TRQ treatment could effectively target the pqs system and subsequently contribute to the inhibition of QS systems in P. aeruginosa.…”
Section: Discussionmentioning
confidence: 91%
“…For example, furanone C-30 (Hentzer et al, 2002), gingerol (Kim et al, 2015) and garlic extract (Rasmussen et al, 2005) have been reported to possess anti-QS activities. Recently, it has been demonstrated that ginkgolic acids from Pistacia lentiscus fruits inhibit P. aeruginosa virulence by targeting the pqs system (Tahrioui et al, 2020). Particularly, many traditional Chinese medicines have been shown to exert anti-QS and anti-virulence activities.…”
Section: Discussionmentioning
confidence: 99%
“…As this is the first report demonstrating the occurence of alkylphenols or alkylsalicylic acids in Pistacia lentiscus L. oil, HPLC-DAD-MS analysis was envisaged with comparison of oil samples 1-14 to the 3-(heptadec-8-en-1-yl)-salicylic acid standard from PLFE1 fruit fraction. PLFE1 is a non-polar fraction rich in alkylsalicylic acids, is isolated from fruits of Algerian Pistacia lentiscus and characterized in a previous work (Tahrioui et al, 2020). PLFE1 contains 3-(heptadec-8-en-1-yl)-salicylic acid, also known as ginkgolic acid (C17:1), together with hydroginkgolic acid (C15:0).…”
Section: Resultsmentioning
confidence: 99%
“…Pyocyanin, a phenazine-derived blue-green pigment is a redox-active secondary metabolite promoting the colonization and the dissemination of the bacterium. The green fluorescent pigment pyoverdine is a Fe 3+ high affinity siderophore [ 53 ]. Iron homeostasis plays a central role in bacterial growth and survival, and P. aeruginosa has developed several strategies to chelate iron from the available environmental iron sources, among which the catechol-derived siderophore pyoverdine.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation for 24 h, cell growth was determined by measuring the OD at 580 nm. A pyocyanin quantification assay was carried out as described previously [ 53 ]. Briefly, one volume of chloroform was used to extract free-cell supernatants samples.…”
Section: Methodsmentioning
confidence: 99%